CART-An Arabic teaching-learning tool for non-native Arabic speakers - Shuib, Ahmad Hasanul Ishraf; Abdul Aziz, Normaziah; Mat Daud, Nuraihan; Hasan, Haslin (IEEE, 2014)
Teaching and learning Arabic language is not an easy task for non-native Arabic speakers. Computer Aided for Language Learning (CALL) has been used by many learning institutions to address this issue. Various teaching-learning techniques and features can be embedded in CALL to compliment the conventional method of language teaching and learning. This paper will describe two useful components i.e. Arabic Readability Index and Online Translation that can be embedded in CALL for Arabic language, which we refer to as CART - CALL with Arabic Readability index and online Translation system.